Pengembangan Video Animasi sebagai Media Pembelajaran untuk Meningkatkan Keterampilan Menyimak Bahasa Jerman Level A1 dengan Menggunakan Animaker pada Topik "Beruf und Jobs” - Sianipar, Santa Rosa; Harahap, Herlina Jasa Putri (Jurnal Intelek Insan Cendikia, 2025)
The aim of this study is to develop a video animation as a learning medium using Animaker on the topic “Professions and Jobs” for the listening subject at the A1 level. This study applies a descriptive-qualitative research method. The development process follows the ADDIE model, which consists of five phases: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The data in this study consist of vocabulary, simple sentences, and short dialogues designed in the form of video animations based on the topic “Professions and Jobs”. The thematic orientation is based on the textbook Netzwerk neu A1, however, all content, including dialogues and exercises, was independently developed by the author. The research was conducted in German language classes in two twelfth-grade classes, namely 12 MIPA 10 and 12 MIPA 8. The result of this study is a series of five video animations in MP4 format aimed at enhancing listening comprehension skills at the A1 level. The developed media were validated by a teacher of German as a foreign language (as a subject matter expert) and a media expert. The evaluations were 92.86 and 95 points respectively, categorized as “Very Good”, indicating that the media is considered suitable for use in school education.